Ag + (at) Eu MOF / HOF-based resonance energy transfer electrochemical luminescence aptamer sensor and application thereof in acetamiprid detection

By synthesizing HOF materials of lanthanides and amplifying the ECL signal using Ag+ catalytic, combined with resonance energy transfer strategy, high efficiency, sensitivity, specificity and stability detection of acetamiprid is achieved, and the detection equipment in the prior art is solved Problems of expensive, complex operation and long detection time.

CN119470587AActive Publication Date: 2025-02-18CHANGZHOU UNIV

Patent Information

Application Number
CN202411589184.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the prior art, when detecting pesticide residues in water bodies, the equipment is expensive, complex in operation and long detection time, making it difficult to achieve efficient, sensitive, simple, convenient and low-cost detection methods.

Method used

Using lanthanide metal ions as the center, sanitide functionalized HOF materials were synthesized by solvothermal method, and the ECL signal was amplified by Ag+ catalytic, combined with the resonance energy transfer strategy, Ag+@Eu MOF/HOF and CdS@Au-cDNA were used. As a luminescent and resonant energy transfer receptor, quantitative analysis of acetamiprid is achieved.

Benefits of technology

It realizes detection of sensitivity, specificity and stability to acetamiprid, overcomes the problems of expensive equipment, complex operation and long detection time of traditional methods, and has the characteristics of high efficiency and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005125104260000011
    Figure HDA0005125104260000011
  • Figure HDA0005125104260000012
    Figure HDA0005125104260000012
  • Figure HDA0005125104260000021
    Figure HDA0005125104260000021
Patent Text Reader

Abstract

The invention belongs to an electrochemiluminescence aptamer sensor, and relates to a resonance energy transfer electrochemiluminescence aptamer sensor based on Ag < + > (at) Eu MOF / HOF and application thereof in acetamiprid detection. A rod-like hydrogen bond organic framework is used as a precursor, and lanthanide Eu < 3 + > is doped. The electrochemical luminescence aptamer sensor for resonance energy transfer is prepared by taking Ag < + > as a co-reactant accelerant, synthesizing Ag < + > (at) Eu MOF / HOF as an energy donor of a resonance energy transfer system and taking leaf-shaped CdS (at) Au-cDNA as an energy receptor. The sensor is used for ACE detection, and has a wide linear range and a low detection limit. The prepared novel Ag < + >-coated Eu MOF / HOF electrochemical luminescence material is applied to electrochemical luminescence detection for the first time and used for detecting acetamiprid residues in water, and an effective and convenient strategy is developed for analysis and detection of pollutants in a water environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemiluminescent aptamer sensors, and specifically relates to a luminescent material Ag + @EuMOF / HOF is used as the luminescent body, and the resonance energy transfer method is used to realize the signal transformation. The leaf-shaped CdS@Au-cDNA is used as the resonance energy transfer acceptor, and the quantitative analysis of acetamiprid is realized according to the regular ECL signal changes. Background Art

[0002] The monitoring and prevention of pesticide residues in water bodies have always been the research focus in the field of environmental chemistry. Acetamiprid (ACE) is a systemic contact insecticide. As a substitute for traditional insecticides such as organophosphates, it is widely used to control piercing-sucking mouthparts pests. Its frequent and widespread use inevitably leads to the accumulation of ACE in soil and water environments, endangering people's health. Therefore, it is very necessary to find an efficient, sensitive, simple, convenient and low-cost ACE detection method. Existing methods for detecting acetamiprid residues include Raman spectroscopy, fluorescence and electrochemical methods. Although these methods meet the detection requirements, they involve expensive equipment, complex operating procedures and long detection time. Therefore, it is crucial to establish a sensitive, simple and reliable acetamiprid rapid detection method to protect human health.

[0003] Electrochemiluminescence combines the advantages of electrochemistry and chemiluminescence, and has the characteristics of small background interference, fast response speed and high sensitivity. Traditional electrochemiluminescent materials such as Ru(bpy)3 2+ , luminol, and quantum dots, etc. However, these traditional luminophores require complicated synthesis steps, have high water solubility resulting in unstable ECL efficiency, or exhibit relatively low ECL emission efficiency due to their π-π stacking effect, which seriously restricts their practical application. Therefore, it is still of great significance and challenge to develop a simple method to prepare high-performance ECL luminophores without causing quenching caused by molecular aggregation.

[0004] HOF materials are self-assembled through organic unit ligands due to hydrogen bonding interactions under the combined action of van der Waals forces, π-π stacking interactions, and electrostatic interactions. In addition to the common advantages of tunable structures, high surface areas, and customized pore sizes similar to other ordered frameworks such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), HOF materials can be constructed under milder conditions with reversible and flexible hydrogen bonds. More importantly, the rich functional sites in HOF materials and the large number of active sites exposed from π-π conjugated linkers can be further assembled with metal ions to synthesize functionalized materials for various fields. However, currently only a small number of HOF materials are used as electrochemiluminescent materials for analytical detection.

[0005] Lanthanide metal-organic framework materials (Ln-MOFs) have the advantages of long luminescence lifetime, strong antenna effect, high specific surface area and active sites, and are an ideal type of ECL probe material. Among them, Eu-MOFs have attracted much attention due to their excellent luminescence properties. However, it is still difficult to obtain a high ECL signal relying solely on the stepped electronic energy levels and 4f-4f transitions of lanthanide elements. In the electrochemiluminescence system, one of the strategies used to amplify ECL is to promote the electroreduction decomposition of co-reactants (such as K2S2O8) on the electrode surface. Co-reaction promoters can interact with co-reactants instead of luminophores to produce more reactive intermediate states, which will increase the oxygen reduction kinetics (ERR) of the luminophore and co-reactant, thereby producing a large number of excited state luminophores and emitting a strong ECL signal. Ag + It has excellent catalytic performance in K2S2O8 activation, Ag + It can promote K2S2O8 to generate more SO4·-, and finally amplify the ECL signal of the system.

[0006] The present invention uses lanthanide metal ions as the core to synthesize lanthanide functionalized HOF materials. The lanthanide ion-induced partial conversion from HOF to MOF is achieved by a solvothermal method, and a Eu MOF / HOF composite material with satisfactory ECL performance is successfully prepared. Ag with catalytic performance is used + , which not only increases the electrochemical active area of ​​HOF materials, but also acts as a co-reactant promoter to amplify the ECL signal of Eu MOF / HOF. The aptamer (apt) of ACE is modified on Ag by π-π conjugation. + @Eu MOF / HOF, used to specifically recognize ACE. CdS@Au-cDNA is used as an energy acceptor in the resonance energy transfer system. CdS@Au-cDNA is modified on the electrode surface through hybridization between cDNA and apt. CdS@Au-cDNA quenches Ag + @EuMOF / HOF's ECL signal causes the ECL signal to change. When the sensor is used for ACE detection, since apt has a higher specificity for ACE, the connection between apt and cDNA is disconnected, CdS@Au-cDNA falls off the electrode, and the resonance energy transfer effect disappears, thereby increasing the ECL signal. The electrochemiluminescent aptamer sensor developed by the present invention can detect ACE with sensitivity, showing high selectivity and stability. Summary of the invention

[0007] The first object of the present invention is to synthesize an electrochemiluminescent body of MOF / HOF material, with lanthanide metal ions as the center, and to realize the partial conversion of HOF to MOF induced by lanthanide ions by solvothermal method, using Ag with catalytic properties+ , which not only increases the electrochemical active area of ​​HOF materials, but also acts as a co-reactant promoter to amplify the ECL signal. + @Eu MOF / HOF has satisfactory ECL performance.

[0008] The second purpose of the present invention is to synthesize CdS@Au-cDNA as an energy acceptor for resonance energy transfer. + @EuMOF / HOF acts as an energy donor for resonance energy transfer. CdS@Au-cDNA can quench Ag + @Eu MOF / HOF ECL signal. The unique leaf structure of CdS provides abundant loading sites for Au NPs, and the two are stably combined through electrostatic adsorption.

[0009] The third object of the present invention is to prepare an electrochemiluminescent aptamer sensor for detecting acetamiprid, wherein the use of the aptamer improves the specificity of the detection, can identify acetamiprid in a complex environment and achieve trace detection.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0011] 1. The present invention discloses a HOF electrochemical luminescent material (Ag + @Eu MOF / HOF) is used as the energy donor in the resonance energy transfer system, and its preparation steps are as follows:

[0012] (1) Preparation of HOF

[0013] Weigh melamine in deionized water, and weigh the corresponding trimesic acid in the above liquid by controlling the molar ratio of melamine to trimesic acid to be 1:1 to 3:1. Stir and heat to 55-95°C until completely dissolved. Then, mix the melamine and trimesic acid solutions and stir at room temperature for 3 hours. Centrifuge at 12000rpm for 10 minutes to collect the crude product, and wash it three times with deionized water. Finally, dry the white powder in vacuum at 660°C for 10 hours.

[0014] (2) Ag + Preparation of @Eu MOF / HOF

[0015] Weigh HOF and Eu(NO3)3·6H2O in deionized water, the mass ratio of HOF and Eu(NO3)3·6H2O is 1:1~3:1, weigh the corresponding AgNO3 according to the molar ratio of Eu(NO3)3·6H2O and AgNO3 of 1:1~5:1, add it to the above solution, stir evenly, add DMF, transfer to a high-pressure reactor and react at 60℃~100℃ for 2h. Centrifuge at 8000rpm for 10min, wash three times with deionized water, and dry the obtained product at 60℃ in vacuum for 10h to obtain a white solid powder. Then, the obtained Ag + @Eu MOF / HOF was dispersed in deionized water to obtain a dispersion of 1-5 mg / mL, which was stored at 4°C for later use.

[0016] Furthermore, in step (1), by controlling the temperature of the synthetic HOF material, the dissolution rate of the raw material melamine can be controlled. When the temperature is too low, melamine cannot dissolve to participate in coordination and bonding. When the temperature rises, the dissolution rate of melamine is accelerated, and the rate of coordination with trimesic acid to form HOF is accelerated, which promotes the formation of HOF. When the temperature is too high, due to the weak thermal stability of the HOF material, the excessively high temperature will destroy the stability of the HOF material. In addition, excessively high temperature will cause the HOF material to generate too fast a rate, and the rod-shaped HOF material will be transformed into a fibrous state, which is not conducive to further generating MOF materials on its surface. Therefore, controlling the temperature at 55 to 95°C can generate an ideal rod-shaped HOF material. The surface of the rod-shaped HOF material has abundant active sites, and a large number of -NH2 and -COOH are distributed on its surface. These groups can coordinate with the lanthanide metal Eu, and finally generate Eu-MOF materials with excellent performance on the surface of the HOF material. Compared with traditional Eu MOF materials, traditional Eu MOF materials usually require high temperature and high pressure environment for synthesis, while HOF material precursor is synthesized first and then Eu is introduced. 3+ , Eu MOF materials can be generated under mild conditions. In addition, rod-shaped HOF can provide a large number of active groups for Eu coordination, which greatly improves the coordination efficiency of Eu.

[0017] Furthermore, in step (2), Ag is added + When Ag + The amount of Ag + It has a positive effect on the ECL performance of Eu MOF / HOF materials. + When the concentration is too low, a small amount of Ag + It cannot significantly promote the Eu MOF / HOF. + When the concentration is too high, excess Ag +It will participate in the bonding of Eu MOF / HOF in large quantities, destroy the stable structure of Eu MOF / HOF, reduce the ECL efficiency of the central atom Eu, and cause the ECL intensity to decrease. Therefore, the molar ratio of Eu(NO3)3·6H2O and AgNO3 is controlled to be 1:1~5:1.

[0018] 2. The synthetic leaf-shaped CdS@Au-cDNA described in the present invention is used as an energy acceptor in the resonance energy transfer system, and its preparation steps are as follows:

[0019] (1) Preparation of AuNPs

[0020] A HAuCl4 solution with a concentration of 0.01wt.% was taken into a round-bottom flask and heated to boiling, and then a sodium citrate solution with a concentration of 1% (w / v) was added dropwise to the HAuCl4 solution, and the volume ratio of the HAuCl4 solution to the sodium citrate solution was controlled to be 100:1 to 100:10, and heated under reflux for 30 minutes, and the solution turned into wine red. The obtained solution containing AuNPs was cooled to room temperature and stored at 4°C for later use. Furthermore, AuNPs can stably exist in a reducing solution containing sodium citrate, and Au NPs can be further centrifuged and purified in subsequent experiments.

[0021] (2) Preparation of CdS

[0022] First, CH4N2S (thiourea) was dissolved in deionized water, and then CdCl2·2.5H2O was added under the condition of controlling the molar ratio of CH4N2S and CdCl2·2.5H2O to be 1:1 to 7:1, and stirred at room temperature for 10 minutes to make it evenly mixed. Then, DMSO was added dropwise to the solution and stirred for 10 minutes. Finally, the solution was transferred to a stainless steel autoclave and reacted at 170°C for 8 to 16 hours. After the autoclave was naturally cooled to room temperature, the orange precipitate at the bottom was washed several times with anhydrous ethanol and deionized water, and dried at 60°C to obtain orange-yellow CdS powder.

[0023] (3) Preparation of CdS@Au-cDNA

[0024] CdS was added to ultrapure water, and the AuNPs solution was added dropwise to the mixture, and the mixture was stirred for 6 hours. Then, the mixture was centrifuged and washed, and vacuum dried at 60°C to obtain CdS@Au. The molar ratio of CdS to AuNPs was controlled to be 10:1 to 20:1 during the preparation of CdS@Au-cDNA.

[0025] cDNA (3 μM) was added to the CdS@Au dispersion, stirred in an ice-water bath for 10 h, the product was centrifuged at 12000 rpm for 15 min, and washed three times with deionized water. The obtained precipitate was dispersed with deionized water to obtain a CdS@Au-cDNA dispersion with a concentration of 1 to 5 mg / mL.

[0026] Furthermore, the amount of added Au NPs was controlled to obtain CdS@Au-cDNA with the best RET effect. This is because too few Au NPs cannot ensure that the leaf-shaped CdS surface is loaded with enough AuNPs to bind to cDNA. If the number of nanoparticles is increased, too many Au NPs will aggregate on the CdS surface, hindering the adsorption of cDNA molecules on the nanoparticles, thereby limiting the ability of cDNA to base pair with apt. The ratio of nanoparticles to CdS is maintained in the above range so that a monolayer of nanoparticles is formed on the surface and there are sufficient adsorption sites to coordinate with the amino groups (-NH2) on the cDNA.

[0027] 3. The preparation steps of the resonance energy transfer system electrochemiluminescence aptamer sensor described in the present invention are as follows:

[0028] (1) The glassy carbon electrode (GCE) was polished and thoroughly cleaned using dilute nitric acid, anhydrous ethanol, and deionized water for 3 minutes respectively;

[0029] (2) Take 5 μL of 0.5-5 mg / mL Ag + @Eu MOF / HOF is added dropwise onto GCE and dried under infrared light to obtain Ag + @EuMOF / HOF / GCE;

[0030] (3) Add 5 μL of apt with a concentration of 1 to 6 μM to the surface of the modified electrode and incubate at 37°C for 6 h to obtain apt / Ag. + @Eu MOF / HOF / GCE;

[0031] (4) 5 μL of 0.5% bovine serum albumin (BSA) was added to block the nonspecific binding sites on the electrode surface. After natural drying, the / BSA / apt / Ag + @Eu MOF / HOF / GCE;

[0032] (5) 1-5 μL CdS@Au-cDNA dispersion was added to the electrode surface and allowed to fully bind with apt at 37°C for 2-8 h to obtain CdS@Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE electrochemiluminescence sensor. Ag in step (2) to step (5) +The volume ratio of @Eu MOF / HOF, apt, bovine serum albumin, and CdS@Au-cDNA dispersion modification solution is 1~5:1~5:1~5:1~5.

[0033] 4. The electrochemiluminescent aptamer sensor prepared in the present invention, wherein the apt sequence of acetamiprid is: 5'-(NH2 C6)-TGT AAT TTG TCT GCA GCG GTT CTT GAT CGC TGA CAC CATATTATG AAG A-3'. The cDNA sequence is: 5'-(NH2 C6)-TCT TCA TAA TAT GG-3'

[0034] 5. The preparation of an electrochemiluminescent aptamer sensor for sensitive detection of acetamiprid according to the present invention is characterized in that the specific detection steps are as follows:

[0035] A1. Preparation of standard solutions containing different concentrations of acetamiprid:

[0036] The acetamiprid solid standard was prepared with deionized water to 1.0 × 10 -3 mol / L solution and diluted into a series of acetamiprid standard solutions with different concentrations, ranging from 1.0×10 -3 ~1.0×10 -17 mol / L;

[0037] A2. Drawing of standard curve:

[0038] A three-electrode system was used, with the prepared electrochemiluminescent aptamer sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. + @Eu MOF / HOF / GCE electrochemiluminescent aptamer sensor was placed in a series of standard solutions of acetamiprid of different concentrations prepared in step A1 and soaked for 10 to 50 minutes (preferably 40 minutes), the electrode was taken out and rinsed with PBS buffer solution, and then naturally dried and subjected to ECL test in PBS buffer solution (0.1M, pH=6.0-9.0) containing 0.1M K2S2O8, and a linear relationship between acetamiprid and the change in electrochemiluminescence intensity (ΔECL) was established, and the corresponding linear regression equation was obtained; wherein the apt sequence of acetamiprid is: 5'-(NH2 C6)-TGTAATTTG TCT GCAGCG GTT CTT GAT CGC TGACAC CAT ATT ATG AAG A-3'. The sequence of cDNA is: 5'-(NH2 C6)-TCT TCA TAA TAT GG-3'.

[0039] A3. Actual sample testing:

[0040] The standard addition method was used to perform ECL testing on acetamiprid in actual samples. The obtained ECL intensity was calculated using the linear regression equation obtained by A2 to obtain the acetamiprid concentration in the sample.

[0041] Beneficial results of the present invention:

[0042] (1) The present invention synthesizes a rod-shaped HOF material by temperature control. The HOF material of this morphology has a large number of active sites, which is conducive to further assembling with metal ions on its surface to synthesize functional materials.

[0043] (2) An electrochemiluminescent material (Ag + @Eu MOF / HOF), the solvothermal method was used to achieve the partial conversion of HOF to MOF induced by lanthanide ions, and Ag + As a co-reactant promoter, it amplifies the ECL signal and broadens the application scope of HOF materials in the field of electrochemiluminescence.

[0044] (3) The present invention adopts a resonance energy transfer strategy to obtain an "off-on-off" ECL signal. This strategy has the significant advantages of high sensitivity and low background noise, overcoming the weakness of false positives caused by a single signal change.

[0045] (4) Leaf-shaped CdS@Au-cDNA was synthesized as a resonance energy transfer acceptor, where the UV-vis spectrum of CdS@Au-cDNA was similar to that of the donor (Ag + The ECL spectra of CdS@Au MOF / HOF) have good overlap, CdS@Au and cDNA are linked by Au-N bonds, and cDNA can specifically recognize specific DNA sequence fragments on the acetamiprid aptamer, thereby improving the specificity of the sensor and the accuracy of detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0047] Figure 1 Based on Ag + Schematic diagram of electrochemiluminescent aptamer resonance energy transfer sensor based on @Eu MOF / HOF for detecting acetamiprid (A: preparation diagram of AuNPs; B: preparation diagram of CdS@Au; C: Ag + @Eu: Preparation diagram of MOF / HOF; D: Brief schematic diagram of sensor preparation).

[0048] Figure 2 : HOF (A), Eu MOF / HOF (B), Ag obtained at 80°C + @Eu MOF / HOF (C) is the SEM image; (D) is the SEM image of HOF obtained under 110°C conditions.

[0049] Figure 3 It is HOF(A), Eu MOF / HOF(B), Ag + @Eu ECL-time curve of MOF / HOF(C).

[0050] Figure 4 Ag was tested in PBS at different pH values. + @Eu ECL intensity of MOF / HOF.

[0051] Figure 5 are SEM images of CdS (A) and CdS@Au (B).

[0052] Figure 6 ECL-time curves of different working electrodes (a: GCE, b: Ag + @Eu MOF / HOF / GCE, c:apt / Ag + @Eu MOF / HOF / GCE,d:BSA / apt / Ag + @Eu MOF / HOF / GCE, e: CdS@Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE, f: ACE / CdS @Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE).

[0053] Figure 7 It is a linear curve of detecting different concentrations of acetamiprid using the prepared electrochemiluminescent aptamer sensor;

[0054] in Figure 7 A is the ECL-time curve of different concentrations of acetamiprid; Figure 7 B is the standard curve of ΔECL and the logarithm of acetamiprid concentration. DETAILED DESCRIPTION

[0055] The present invention is further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0056] Example 1

[0057] 1. A method for preparing a HOF material electrochemical luminescent body, comprising the following steps:

[0058] (1) Preparation of HOF

[0059] Dissolve 0.5 mmol melamine and 0.5 mmol trimesic acid in 50 mL deionized water, respectively, and heat to 80°C with stirring until completely dissolved. Then, mix the melamine and trimesic acid solutions and stir at room temperature for 1 hour. Centrifuge at 12000 rpm for min to collect the crude product and wash it three times with deionized water. Finally, dry the white powder under vacuum at 60°C for 12 hours.

[0060] (2) Ag + Preparation of @Eu MOF / HOF

[0061] Weigh 25 mg HOF, 0.04 mmol Eu(NO3)3·6H2O, and 0.01 mmol AgNO3 and dissolve them in 10 mL deionized water. Stir evenly and add 2 mL DMF. Transfer to a 25 mL autoclave and react at 80°C for 2 h. Centrifuge at 8000 rpm for 10 min and wash three times with deionized water. The obtained product is vacuum dried at 60°C for 10 h to obtain a white solid powder. Then, the obtained Ag + @Eu MOF / HOF was dispersed in deionized water to obtain a 2 mg / mL dispersion, which was stored at 4°C for later use.

[0062] 2. Prepare Ag + @Eu MOF / HOF for ECL detection

[0063] (1) Preparation of electrochemiluminescence sensor

[0064] 1) A glassy carbon electrode with a diameter of 3 mm was polished with 0.3 μm and 0.05 μm Al2O3 powders, respectively, and then ultrasonically cleaned with 1% dilute nitric acid and deionized water for 3 min, and finally the surface was dried with N2;

[0065] 2) Add 5 μL of 2 mg / mL Ag + @Eu MOF / HOF was drop-coated on the GCE surface and dried naturally to obtain Ag + @EuMOF / HOF / GCE;

[0066] (2) The electrochemiluminescence sensor of the present invention is used for ECL detection

[0067] (1) The prepared Ag + @Eu MOF / HOF / GCE was used as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode for ECL testing;

[0068] (2) The parameters of the electrochemiluminescence detection instrument were set as follows: the scanning rate was set to 100 mV / s, and the photomultiplier tube high voltage was set to 800 V;

[0069] (3) The electrochemical workstation parameters were set as follows: the cyclic voltammetry scan voltage range was 0 to -1.8 V; the scan rate was set to 100 mV / s;

[0070] (4) Using a PBS buffer solution containing K2S2O8, the intensity of the generated electrochemiluminescence signal was recorded; the PBS buffer solution was: a 0.1 mol / L Na2HPO4 / NaH2PO4 buffer solution with a pH of 7.5 containing 0.1 mol / L K2S2O8.

[0071] Comparative Example 1

[0072] 1. A method for preparing a HOF material electrochemical luminescent body, comprising the following steps:

[0073] (1) Preparation of HOF

[0074] Dissolve 0.5 mmol melamine and 0.5 mmol trimesic acid in 50 mL deionized water, respectively, and heat to 80°C with stirring until completely dissolved. Then, mix the melamine and trimesic acid solutions and stir at room temperature for 1 hour. Centrifuge at 12000 rpm for min to collect the crude product and wash it three times with deionized water. Finally, dry the white powder under vacuum at 60°C for 12 hours.

[0075] (2) Preparation of Eu MOF / HOF

[0076] Weigh 25 mg HOF and 0.04 mmol Eu(NO3)3·6H2O and dissolve them in 10 mL deionized water. Stir well and add 2 mL DMF. Transfer to a 25 mL autoclave and react at 80°C for 2 h. Centrifuge at 8000 rpm for 10 min and wash three times with deionized water. The obtained product is vacuum dried at 60°C for 10 h to obtain a white solid powder. Then, the obtained Ag + @Eu MOF / HOF was dispersed in deionized water to obtain a 2 mg / mL dispersion, which was stored at 4°C for later use.

[0077] 2. Use the prepared HOF or Eu MOF / HOF for ECL detection

[0078] (1) Preparation of electrochemiluminescence sensor

[0079] (I) A glassy carbon electrode (GCE) with a diameter of 3 mm was polished and then thoroughly cleaned using dilute nitric acid, anhydrous ethanol, and deionized water for 3 minutes respectively;

[0080] (II) 5 μL of HOF or Eu MOF / HOF with a concentration of 2 mg / mL was drop-coated on the GCE surface and dried naturally to obtain HOF / GCE;

[0081] (2) The electrochemiluminescence sensor of the present invention is used for ECL detection

[0082] (I) The prepared HOF / GCE and Eu MOF / HOF / GCE were used as working electrodes, platinum wire as counter electrode, and Ag / AgCl as reference electrode to perform ECL test;

[0083] (II) The parameters of the electrochemiluminescence detection instrument were set as follows: the scan rate was set to 100 mV / s, and the photomultiplier tube high voltage was set to 800 V;

[0084] (III) The electrochemical workstation parameters were set as follows: the cyclic voltammetry scan voltage range was 0 to -1.8 V; the scan rate was set to 100 mV / s;

[0085] (IV) Using a PBS buffer solution containing K2S2O8, the intensity of the generated electrochemiluminescent signal was recorded; the PBS buffer solution was a 0.1 mol / LNa2HPO4 / NaH2PO4 buffer solution with a pH of 7.5 containing 0.1 mol / L K2S2O8.

[0086] Figure 2 A is the prepared HOF, Eu MOF / HOF, Ag + @Eu SEM image of MOF / HOF, Figure 1 A is the SEM image of HOF, and its surface appears as long and thin nanowires. Figure 2 B is the morphology of Eu MOF / HOF, and Eu 3+ After coordination, HOF changes from a linear shape with a diameter of about 80nm to a rough rod shape with a diameter of about 600nm. This transformation maintains the original rod-like characteristics of HOF, and many newly generated fine particles are attached to its surface. These fine irregular particles are generated on the surface of HOF material by Eu 3+ Induce the generated MOF materials. Figure 2 C is Ag + @Eu MOF / HOF SEM image, we can see that Ag + After coordination, the morphology of Eu MOF / HOF is not changed. + The ionic form is fixed on the HOF material through Ag-amino coordination bonds.

[0087] Figure 3 The prepared HOF / GCE, Eu MOF / HOF / GCE, Ag +@Eu MOF / HOF / GCE electrode ECL test obtained by ECL-time curve. As can be seen from the figure, the ECL value of HOF / GCE is about 12000a.u. (curve a), the ECL value of EuMOF / HOF / GCE is about 25000a.u. (curve b), and the ECL value of Ag + @Eu The ECL value of MOF / HOF / GCE is about 46000 a.u. (curve c). By comparison, Ag + @Eu MOF / HOF / GCE has the best performance. Lanthanide elements can improve the ECL performance of HOF materials. This is because the lanthanide element Eu 3+ As the main ECL center, it can emit a strong signal in the co-reaction medium of K2S2O8 due to the ligand antenna effect between HOF and ligands. + Ag is fixed on the HOF material through Ag-amino coordination bonds. + The ECL value of Eu MOF / HOF will be further improved due to the Ag + As a metal catalyst, it can catalyze the decomposition of K2S2O8 into SO4 - , thereby amplifying Ag + @Eu ECL signal of MOF / HOF.

[0088] Comparative Example 2

[0089] 1. The preparation steps of HOF precursor are as follows:

[0090] Dissolve 0.5 mmol melamine and 0.5 mmol trimesic acid in 50 mL deionized water, respectively, and heat to 110°C with stirring until completely dissolved. Then, mix the solutions of melamine and trimesic acid and stir at room temperature for 1 hour. Collect the crude product by centrifugation at 12000 rpm and wash it three times with deionized water. Finally, dry the white powder under vacuum at 60°C for 12 hours.

[0091] The stirring temperature was set to 110°C, and the SEM image of the obtained HOF material was as follows: Figure 2 D. By Figure 2 D shows that when the temperature is too high, the obtained HOF material is a thin and long nanofiber, which is not conducive to the formation of MOF material induced by lanthanide central atom Eu on its surface. + @Eu The ECL intensity of MOF / HOF is also low (ECL≈9000a.u.).

[0092] Comparative Example 3

[0093] 1. A method for preparing a HOF material electrochemical luminescent body, comprising the following steps:

[0094] Prepare Ag according to the method of Example 1 + @Eu MOF / HOF / GCE.

[0095] 2. Prepare Ag + @Eu MOF / HOF for ECL detection

[0096] (1) Preparation of electrochemiluminescence sensor

[0097] 1) A glassy carbon electrode (GCE) with a diameter of 3 mm was polished and thoroughly cleaned using dilute nitric acid, anhydrous ethanol and deionized water for 3 minutes respectively;

[0098] 2) Add 5 μL of 2 mg / mL Ag + @Eu MOF / HOF was drop-coated on the GCE surface and dried naturally to obtain Ag + @EuMOF / HOF / GCE;

[0099] (2) The electrochemiluminescence sensor of the present invention is used for ECL detection

[0100] (1) The prepared Ag + @Eu MOF / HOF / GCE was used as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode for ECL testing;

[0101] (2) The parameters of the electrochemiluminescence detection instrument were set as follows: the scanning rate was set to 100 mV / s, and the photomultiplier tube high voltage was set to 800 V;

[0102] (3) The electrochemical workstation parameters were set as follows: the cyclic voltammetry scan voltage range was 0 to -1.8 V; the scan rate was set to 100 mV / s;

[0103] (4) Using a PBS buffer solution containing K2S2O8, the intensity of the generated electrochemiluminescence signal was recorded; the PBS buffer solution: a 0.1 mol / LNa2HPO4 / NaH2PO4 buffer solution containing 0.1 mol / LK2S2O8, with pH values ​​selected from 6.0, 6.5, 7.0, 8.0, 8.5, and 9.0, respectively.

[0104] Ag + @Eu MOF / HOF ECL-time curves under different pH conditions are shown in Figure 4As can be seen from the figure, the ECL value gradually increases in the range of pH = 6.0 to 7.5, reaching a maximum value of about 46000 a.u. at pH = 7.5, and then ECL decreases with the increase of pH. This is mainly because when the pH is less than 7.5, the protons around the electrode are easily reduced to H2, which inhibits the S2O8 2- The reduction of SO4 ·- The generation of SO4 is reduced, which ultimately reduces the ECL intensity. Under alkaline conditions, excess anions are dispersed around the electrode, preventing SO4 ·- Close to the electrode surface, resulting in a decrease in the ECL signal. Therefore, the pH value was selected as 7.5 throughout the experiment.

[0105] Example 2

[0106] The preparation method of the resonance energy transfer acceptor CdS@Au-cDNA has the following specific steps:

[0107] (1) Preparation of AuNPs

[0108] 0.01% HAuCl4 (100 mL) was heated to boiling at 120°C, and then 3.5 mL 1% (w / v) sodium citrate was added to the solution and heated under reflux for 30 min until the solution turned into wine red. The obtained AuNPs were cooled to room temperature and stored at 4°C for later use.

[0109] (2) Preparation of CdS

[0110] First, weigh 0.475g of CdCl2·2.5H2O and 0.152g of CH4N2S (thiourea) and dissolve them in 70mL of deionized water, and stir them at room temperature for 10min to mix them evenly. Then, add 0.3mL of DMSO to the solution and stir for 10min. Finally, transfer the solution to a 100mL polytetrafluoroethylene-lined stainless steel autoclave and react in a 170℃ drying oven for 8h. After the autoclave is naturally cooled to room temperature, wash the orange precipitate at the bottom with anhydrous ethanol and deionized water several times, and dry it at 60℃ to obtain orange-yellow CdS powder.

[0111] (3) Preparation of CdS@Au-cDNA

[0112] 3 mg of CdS was added to 3 mL of ultrapure water, and 2 mL of 0.22 mM Au NPs solution was gradually added to the mixture, and the mixture was stirred continuously for 6 h. Then, the mixture was centrifuged and washed, and vacuum dried at 60 ° C to obtain CdS@Au. 70 μL of cDNA (3 μM) was added to the CdS@Au dispersion, stirred in an ice water bath for 10 h, the product was centrifuged at 12000 rpm for 15 min, and washed three times with deionized water. The obtained precipitate was dispersed with deionized water to obtain a CdS@Au-cDNA dispersion with a concentration of 1 mg / mL.

[0113] Figure 5 The SEM images of CdS and CdS@Au are shown in Figure 2. By comparing the morphology of the two images, it can be seen that CdS exhibits a unique leaf-like structure ( Figure 5 A), which can provide abundant binding sites for AuNPs. Many fine particles ( Figure 5 B), these newly emerged particles are a large number of AuNPs loaded on the surface of CdS.

[0114] Example 3

[0115] 1. A Ag-based + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor is used for the detection of acetamiprid. The preparation process of the sensor is as follows:

[0116] According to the method in Example 1, Ag was prepared + @Eu MOF / HOF, CdS@Au-cDNA was prepared according to the method in Example 2. 5 μL of Ag with a concentration of 2 mg / mL was added + @Eu MOF / HOF drop coating on GCE surface to obtain Ag + @Eu MOF / HOF / GCE. Then 5 μL of 3 μM apt was added to the electrode surface and incubated at 37°C for 6 h to obtain apt / Ag + @Eu MOF / HOF / GCE. Then, 5.0 μL of 0.5% bovine serum albumin (BSA) was added to block the nonspecific binding sites on the electrode surface. Then, 5 μL of 2 mg / mL CdS@Au-cDNA was added to the electrode surface and fully combined with apt at 37°C for 2 h to obtain CdS@Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE. Finally, the obtained sensor was immersed in 10 -10 The electrode was placed in ACE solution containing 0.1 M for 40 min, then taken out, rinsed with PBS solution, and tested in PBS containing 0.1 M K2S2O8 (0.1 M, pH = 7.5).

[0117] 2.ECL test

[0118] (1) ECL test was performed using a bare GCE with a diameter of 3 mm and the modified electrode prepared in each step as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl as the reference electrode;

[0119] (2) The parameters of the electrochemiluminescence detection instrument were set as follows: the scanning rate was set to 100 mV / s, and the photomultiplier tube high voltage was set to 800 V;

[0120] (3) The electrochemical workstation parameters were set as follows: the cyclic voltammetry scan voltage range was 0 to -1.8 V; the scan rate was set to 100 mV / s;

[0121] (4) Using a PBS buffer solution containing K2S2O8, the intensity of the generated electrochemiluminescence signal was recorded; the PBS buffer solution was: a 0.1 mol / L Na2HPO4 / NaH2PO4 buffer solution with a pH of 7.5 containing 0.1 mol / L K2S2O8.

[0122] Figure 6 It is the ECL intensity curve of each modified electrode. It can be seen from the figure that the ECL intensity of bare GCE is ≈1600a.u. (curve a). + @Eu The ECL intensity of MOF / HOF / GCE increased significantly to ≈46000 a.u. (curve b), which indicates that Ag + @Eu MOF / HOF was successfully modified on the electrode and had a strong ECL signal. After modification with apt and BSA, the ECL signal dropped to ≈44650 a.u. (curve c) and ≈40000 a.u. (curve d), respectively. Subsequently, the acceptor CdS@Au-cDNA was added to the electrode surface, and the ECL intensity dropped significantly to 10200 a.u. (curve e). This is because the donor Ag + The resonance energy transfer between Ag@Eu MOF / HOF and the acceptor CdS@Au makes Ag@Eu + The ECL intensity of @Eu MOF / HOF weakened. Finally, the prepared sensor was immersed in a 1×10 -10 M ACE, the electrode was taken out and PBS was used to wash away the incompletely bound ACE, and the ECL value was tested to be ≈320000 a.u. (curve f). This is because apt specifically binds to the detected ACE, replacing the weaker interaction between apt and cDNA, causing CdS@Au-cDNA to fall off the electrode, the resonance energy transfer effect disappears, and the ECL intensity rises. The above results show that the electrochemiluminescence sensor was successfully prepared and can be used for the detection of ACE.

[0123] Example 4

[0124] 1. A Ag-based + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor is used for the detection of acetamiprid. The preparation steps of the sensor are as follows:

[0125] According to the method in Example 1, Ag was prepared + @Eu MOF / HOF, CdS@Au-cDNA was prepared according to the method in Example 2. 5 μL of Ag with a concentration of 2 mg / mL was added + @Eu MOF / HOF drop coating on GCE surface to obtain Ag + @Eu MOF / HOF / GCE. Then 5 μL of 3 μM apt was added to the electrode surface and incubated at 37°C for 6 h to obtain apt / Ag + @Eu MOF / HOF / GCE. Then 5.0 μL 0.5% bovine serum albumin (BSA) was added to block the nonspecific binding sites on the electrode surface. Then 5 μL of 2 mg / mL CdS@Au-cDNA was added to the electrode surface and fully combined with apt at 37°C for 2 h to obtain CdS@Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE electrochemiluminescent aptamer sensor.

[0126] A1. Preparation of standard solutions containing different concentrations of acetamiprid:

[0127] The acetamiprid solid standard was prepared with deionized water to 1.0 × 10 -3 mol / L solution and diluted into a series of acetamiprid standard solutions with different concentrations, ranging from 1.0×10 -3 ~1.0×10 -17 mol / L;

[0128] A2. Drawing of standard curve:

[0129] A three-electrode system was used, with the prepared electrochemiluminescent aptamer sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. The prepared electrochemiluminescent aptamer sensor was placed in a series of standard solutions of different concentrations of acetamiprid prepared in step A1 and soaked for 40 minutes. The electrode was taken out and rinsed with PBS buffer solution. After natural drying, an electrochemiluminescence test was performed in a PBS buffer solution (0.1M, pH=7.5) containing 0.1M K2S2O8 to establish a linear relationship between acetamiprid and the change in electrochemiluminescence intensity (ΔECL), and the corresponding linear regression equation was obtained; the parameters of the electrochemiluminescence detection instrument were set as follows: the scanning rate was set to 100mV / s, and the photomultiplier tube high voltage was set to 800V; the parameters of the electrochemical workstation were set as follows: the cyclic voltammetry scanning voltage range was 0 to -1.8V; the scanning rate was set to 100mV / s;

[0130] Figure 7 A is based on the luminescent Ag + @Eu MOF / HOF prepared electrochemiluminescent aptamer sensor (CdS@Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE) was used to detect acetamiprid. As can be seen from the figure, when the acetamiprid concentration was 10 -8 ~10 -15 Within the range of M, the ECL value first increases with the increase of acetamiprid concentration. Figure 7 B is the linear regression curve of the ECL change value (ΔECL) of the sensor and the logarithm of the acetamiprid concentration. The two show a good linear relationship. The linear regression equation is ΔECL = 41351.19048 + 2020.19048 × lgC, R 2 =0.9983, the detection limit is 7.33×10 -16 M(3σ / slope).

[0131] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A Ag-based + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor, characterized in that Including as a donor to modify the electrode surface Ag + @Eu MOF / HOF luminescent material, aptamer apt modified on the surface of Ag+@Eu MOF / HOF luminescent material, and bovine serum albumin, as a receptor, modified CdS@Au-cDNA on the electrode surface to obtain CdS@Au-cDNA / BSA / apt / Ag + @Eu MOF / HOF / GCE aptamer sensor; CdS@Au-cDNA and Ag + @Eu A resonance energy transfer mechanism is formed between MOF / HOF.

2. According to claim 1, based on Ag + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor, characterized by: Take Ag + @Eu MOF / HOF dispersion was added dropwise onto GCE and dried under infrared light to obtain Ag + @EuMOF / HOF / GCE modified electrode; apt was added to the surface of the modified electrode and incubated to obtain apt / Ag + @Eu MOF / HOF / GCE; add bovine serum albumin and dry naturally to obtain BSA / apt / Ag + @Eu MOF / HOF / GCE; finally, CdS@Au-cDNA is added dropwise to the electrode surface to obtain the resonance energy transfer electrochemiluminescence aptamer sensor.

3. According to claim 2, based on Ag + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor, characterized by: Ag + @Eu MOF / HOF preparation steps are as follows: (1) Preparation of HOF Weigh melamine in deionized water, weigh trimesic acid and add it to the above liquid, stir and heat until completely dissolved, collect the crude product by centrifugation, wash and dry; wherein the molar ratio of melamine to trimesic acid is 1:1 to 3:1; (2) Ag + Preparation of @EuMOF / HOF Weigh HOF and Eu(NO3)3·6H2O in deionized water, add AgNO3, After stirring evenly, add DMF, transfer to a high-pressure reactor and react at 60℃~100℃ for 2h, centrifuge, wash, and dry to obtain a white solid powder, which is Ag. + @EuMOF / HOF, disperse it in deionized water to obtain a dispersion, and store it at low temperature for later use; wherein the molar ratio of Eu(NO3)3·6H2O and AgNO3 is 1:1 to 5:1; the mass ratio of HOF and Eu(NO3)3·6H2O is 1:1 to 3:

1.

4. According to claim 2, based on Ag + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor, characterized by: The preparation method of CdS@Au-cDNA is as follows: weigh CdS and add it to ultrapure water, add AuNPs solution dropwise thereto, and stir and mix continuously, then centrifuge and wash the mixture, and vacuum dry to obtain CdS@Au; add cDNA to the CdS@Au dispersion, stir in an ice water bath, centrifuge and wash the product, and disperse the obtained precipitate with deionized water to obtain a CdS@Au-cDNA dispersion.

5. The method according to claim 1 based on Ag + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor, characterized by: The concentration of Ag was 2 mg / mL. + @Eu MOF / HOF drop coating on GCE surface to obtain Ag + @Eu MOF / HOF / GCE. Then 3 μM apt was added to the electrode surface and incubated at 37°C for 6 h to obtain apt / Ag + @Eu MOF / HOF / GCE; then add 0.5% bovine serum albumin by volume, and then add CdS@Au-cDNA dispersion to the electrode surface, and fully combine with apt at 37°C for 2 hours.

6. The Ag-based + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor is used for the detection of acetamiprid, characterized in that: The electrochemiluminescent aptamer sensor according to claim 1 is used as a working electrode, a platinum wire is used as a counter electrode, and Ag / AgCl is used as a reference electrode. In a three-electrode system, the concentration of acetamiprid is detected by electrochemiluminescence detection method; the sequence of the DNA chain of apt is: 5'-(NH2 C6)-TGT AAT TTGTCT GCA GCG GTT CTT GAT CGC TGA CAC CAT ATTATG AAG A-3′; the sequence of cDNA is 5'-(NH2C6)-TCT TCATAATATGG-3.

7. The Ag-based + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor is used for the detection of acetamiprid, characterized in that: (1) Preparation of standard solutions containing different concentrations of acetamiprid: The acetamiprid solid standard was prepared with deionized water to a concentration of 1.0 × 10 -3 mol / L solution and diluted into a series of acetamiprid standard solutions with different concentrations, ranging from 1.0×10 -3 ~1.0×10 -17 mol / L; (2) using a three-electrode system, with the prepared electrochemiluminescent aptamer sensor as the working electrode, platinum wire as the counter electrode, and Ag / AgCl as the reference electrode, the prepared electrochemiluminescent aptamer sensor is placed in a series of standard solutions of different concentrations of acetamiprid prepared in step (1) and immersed for 10 to 50 minutes, the electrode is taken out and rinsed with PBS buffer solution, and after natural drying, an ECL test is performed in a PBS buffer solution containing 0.1M K2S2O8, a linear relationship between acetamiprid and the change in electrochemiluminescence intensity is established, and the corresponding linear regression equation is obtained; (3) The acetamiprid in the actual sample is subjected to an ECL test using the standard addition method. The obtained ECL intensity is calculated using the linear regression equation obtained in step (2) to obtain the acetamiprid concentration in the sample.

8. The Ag-based + @Eu MOF / HOF resonance energy transfer electrochemiluminescence aptamer sensor is used for the detection of acetamiprid, characterized in that: The pH of the PBS buffer solution is 6.0-9.0, and the concentration is 0.1M.

Citation Information

Patent Citations

  • Method for detecting acetamiprid in waste water by chemiluminiscence

    CN105572107A

  • Method for detecting acetamiprid based on triple-helical DNA molecular switch

    CN106153588A

  • Method for preparing electrochemiluminescent aptamer sensor based on resonance energy transfer

    CN110186911A

  • Sensor for detecting acetamiprid based on electrochemical luminescence method as well as preparation method and application

    CN112098484A

  • Method for detecting ferric ions and glutathione based on HOF-PyTTA fluorescent material

    CN113791056A

Cited By

  • Preparation method of PFC-1-UiO-66 heterojunction nano-enzyme and application of PFC-1-UiO-66 heterojunction nano-enzyme in multi-mode detection of catechol

    CN120908372A